Determinants of Dietary Adherence Among Type 2 Diabetes Patients Aimed COVID-19 at the University of Gondar Comprehensive Specialized Hospital - Mekonnen, Chilot Kassa (Diabetes Metab Syndr Obes, 2021)
BACKGROUND: People with diabetes are proving to be at higher risk of severe coronavirus infection than the general population. Non-adherence to dietary recommendation is a critical problem in individuals with type 2 diabetes; particularly, in the era of coronavirus. This study aimed to explore determinants that affect adherence to the recommendations of diet during coronavirus pandemic. OBJECTIVE: This study aimed to determine dietary adherence among diabetes type 2 patients aimed at coronavirus pandemic and its associated factors. METHODS: An institutional-based cross-sectional study was conducted among type 2 diabetes patients on follow-up. Systematic random sampling was employed to get representative study participants. Dietary adherence was dichotomized and with logistic regression analysis to assess the association between dependent and explanatory variables. The degree of association was interpreted by using both crude odds ratios and adjusted odds ratios with 95% confidence intervals and P-values <0.05 were considered statistically significant. RESULTS: In this study, 576 participants took part with a 99.3% response rate. The dietary adherence was found to be 48.3% with [95% CI (44.1–52.4)]. The educational level of College and above was [AOR=3.64, 95% CI (1.59–8.34)], being a government-employed [AOR=2.38, 95% CI (1.13–4.99)], being urban [AOR=1.30, 95% CI (1.09–2.42)], family size of less than five [AOR=1.27, 95% CI (1.08–1.97)], medium level of wealth-status[AOR=2.26, 95% CI (1.67–4.54)], family history of diabetes [AOR=2.18, 95% CI (1.14–4.19)], duration of diabetes more than 15 years [AOR=5.39, 95% CI (1.57–18.52)], and knowledge related to coronavirus [AOR=4.33,95% CI (2.71–6.92)] were significantly associated with adherence to the dietary recommendation. CONCLUSION: The dietary adherence was relatively low aimed at coronavirus pandemic. Knowledge about COVID-19 was found significantly associated with dietary adherence. RECOMMENDATIONS: There has to be a strong commitment to aware the community to minimize the risk of coronavirus severity among diabetes patients. This could be through adherence to dietary recommendations of particularly in the era of coronavirus pandemic.